Abundance and Diversity of Bacteria on Catfish Nursery Rearing (Clarias gariepinus) With Closed Water System (Close Water System) - Muhammad Hanif Azhar; Mohammad Faizal Ulkhaq; . Prayogo (Airlangga University, 2017)
This research aimed to identify types of bacteria existed in nursery rearing pond of catfish (Clarias gariepinus) using closed water system. The observed data include bacterial abundance and diversity in the water and in the fish digestion system, fish growth and water quality. This research was performed in the media of 3 concrete pools with the size of 3 x 1 x 0.8 m3 containing fish stock spreading of 3000 tail / pond. The obtained results showed that the highest abundance of bacteria was found in the surface and the bottom of pond C with the abundance number of 3,0 x 104and 1,2 x 103for aerobic and anaerobic bacteria, respectively. Moreover, it was figured that the dominant bacterial species found in the water and the gastrointestinal tract were from the genus of Bacillus, Clostridium and Lactobacillus. Meanwhile, water quality in the pond was observed in the normal range with the temperatures of 28 - 30 oC, pH (6.0 - 7.0), DO (4.5 - 5.7 ppm), ammonia (0.06 - 0.03 ppm), nitrite (0 ppm) and nitrate (0 - 5 ppm). Keywords: Type of bacteria, catfish (Clarias gariepinus), Closed water system.